53‐2: Highly Self‐healable Coating Materials with Improved Mechanical Surface Properties for Flexible Electronic Displays. Issue 1 (29th May 2019) - Lee, Sung Ku; Hong, Sung Woo
Abstract : A new self‐healable coating material is prepared by blending conventional polyurethane and functional polyimide. The blended coating material has outstanding self‐healing abilities and, interestingly, significantly increased surface hardness and modulus compared with polyurethane only, which is attributed to the strong supramolecular networks resulting from interactions between polyurethane and functional polyimide.